REINTERPRETING THE KUTIKA MANUSCRIPT: A BUGINESE ETHNOECOLOGICAL PERSPECTIVE - Widyaningrum, Rahmatia Ayu; Limbong, Priscila Fitriasih; Pudjiastuti, Titik; Buduroh, Mamlahatun -, - (UI Scholars Hub, 2026)
This article offers a reinterpretation of the Kutika manuscript from a Buginese ethnoecological perspective. Departing from a philological study of the Lontara’ Kutika text in the National Library of Indonesia (PNRI) collection (code VT 129), this research examines how Buginese communities articulate their interaction with nature through this manuscript. The Kutika text has generally been understood merely as a book of time calculation, yet its background is imbued with philosophical values that show how the Buginese talk to nature, read signs, and treat nature as an equal element rather than a mere object. Using the framework of human ecology, this study describes the ethnoecological concepts embedded in the Kutika text. Philosophically, human ecology is built upon an ontological view that does not separate humans from their environment. Humans see themselves as an integral part of an ecosystem, a living space with functional relationships between social and biophysical systems that cannot be separated. This view is in line with Buginese beliefs that every natural element has a spirit and exerts influence on human life. The research specifically aims to interpret the maritime traditions contained in the Kutika text from a human ecological perspective. More broadly, it contributes to scholarship by introducing local knowledge of the Bugis community, derived from centuries of observation and reflection, which remains applicable to contemporary discussions of human–environment relations.